2003
DOI: 10.1128/aem.69.2.1043-1050.2003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Fungal Production and Biomass on Standing Dead Scirpus lacustris Litter in a Northern Prairie Wetland

Abstract: Decaying macrophytes are an important source of carbon and nutrients in fungal and bacterial communities of northern prairie wetlands. Dead macrophytes do not collapse into the water column immediately after death, and decomposition by fungi and bacteria begins while the plants are standing. The seasonal variations in fungal biomass and production on Scirpus lacustris stems, both above and below water, were measured to assess which environmental factors were dominant in affecting these variations in a typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
3
13
0
1
Order By: Relevance
“…Despite abundant evidence of standing litter accumulation in freshwater marsh habitats and extensive fungal colonization, few studies have quantified rates of carbon flow into fungi during standing litter decomposition (Newell et al 1995;Findlay et al 2002;Verma et al 2003) or assessed their potential contribution to plant litter carbon and nutrient transformations (Gessner et al 2007). As a result, fungal decay processes within standing litter compartments of freshwater marshes have not been recognized as a potential pathway in wetland biogeochemical cycles (Mitsch and Gosselink 2007).…”
mentioning
confidence: 99%
“…Despite abundant evidence of standing litter accumulation in freshwater marsh habitats and extensive fungal colonization, few studies have quantified rates of carbon flow into fungi during standing litter decomposition (Newell et al 1995;Findlay et al 2002;Verma et al 2003) or assessed their potential contribution to plant litter carbon and nutrient transformations (Gessner et al 2007). As a result, fungal decay processes within standing litter compartments of freshwater marshes have not been recognized as a potential pathway in wetland biogeochemical cycles (Mitsch and Gosselink 2007).…”
mentioning
confidence: 99%
“…Both studies reported the temperature as the most important environmental factor for the cellulose decay. Additionally, Verma et al (2003) reported the direct proportionality between the temperature and the development of aquatic fungal populations, suggesting the temperature as the key factor to seasonal changes in fungal growth and activity.…”
Section: Discussionmentioning
confidence: 97%
“…The S. la- custris we used was from the previous year's stand and was standing dead on the periphery of Pond 50 when harvested. This means that from the time they died to when we harvested them they were exposed to the environment and, under favorable conditions, would have been colonized and decomposed by microbes (Verma et al 2003). The decomposition would not have occurred homogeneously over the entire surface of the stem, but rather in patches, resulting in a patchwork pattern with some parts of the stem decomposed while other parts would have remained intact.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic litter decomposition is dominated by fungi, accounting for 63 to 99% of the total microbial biomass and production (Gessner & Newell 2002, Hieber & Gessner 2002, Verma et al 2003. The variability in fungal dominance may be due to the nature and carbon content of the plant substrate (Gessner et al 1993, Baldy et al 1995, Gulis 2001, Mille-Lindblom et al 2006b), the nature of the aquatic system or because of bacterial competition and inhibition (Moller et al 1999, Gulis & Suberkropp 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation